1.5 μm lidar anemometer for true air speed, angle of sideslip, and angle of attack measurements on-board Piaggio P180 aircraft. (11th April 2016) - Augere, B; Besson, B; Fleury, D; Goular, D; Planchat, C; Valla, M
Abstract: Lidar (light detection and ranging) is a well-established measurement method for the prediction of atmospheric motions through velocity measurements. Recent advances in 1.5  μ m Lidars show that the technology is mature, offers great ease of use, and is reliable and compact. A 1.5  μ m airborne Lidar appears to be a good candidate for airborne in-flight measurement systems. It allows measurements remotely, outside aircraft aerodynamic disturbance, and absolute air speed (no need for calibration) with great precision in all aircraft flight domains. In the framework of the EU AIM2 project, the ONERA task has consisted of developing and testing a 1.5  μ m anemometer sensor for in-flight airspeed measurements. The objective of this work is to demonstrate that the 1.5  μ m Lidar sensor can increase the quality of the data acquisition procedure for aircraft flight test certification. This article presents the 1.5  μ m anemometer sensor dedicated to in-flight airspeed measurements and describes the flight tests performed successfully on-board the Piaggio P180 aircraft. Lidar air data have been graphically compared to the air data provided by the aircraft flight test instrumentation (FTI) in the reference frame of the Lidar sensor head. Very good agreement of true air speed (TAS) by a fraction of ms −1, angle of sideslip (AOS), and angle of attack (AOA) by a fraction of degree were observed.